Tarsal tunnel syndrome in patients with fibromyalgia - Yoon-Sik JO; Bora YOON; Jun Yeong HONG; Chung-Il JOUNG; Yuseok KIM; Sang-Jun NA (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the frequency of tarsal tunnel syndrome (TTS) in fibromyalgia (FM) patients. Patients and methods: In this prospective study, we investigated paresthesia of the foot, sensory and motor deficits, atrophy of the abductor hallucis muscle, and the presence of Tinel’s sign in 76 female FM patients (mean age 39.3±7.4 years; range, 24 to 52 years) and 60 sex-matched healthy control subjects (mean age 38.6±8.2 years; range, 28 to 49 years) without FM between July 2016 and June 2018. Bilateral electrophysiological studies of the tibial, peroneal, sural, and medial as well as lateral plantar nerves were performed. Results: Paresthesia was observed in 22 FM patient extremities and four control subject extremities (p=0.002). Local tenderness at the tarsal tunnel was observed in 12 FM patient extremities and two control subject extremities (p=0.021). TTS was detected electrophysiologically in 14 FM patient extremities and two control subject extremities (p=0.009). Conclusion: Paresthesia of the foot and local tenderness at the tarsal tunnel were significantly more prevalent in FM patients than in healthy control subjects. TTS is statistically more frequent in patients with FM than the normal population. The potential comorbidities of TTS and paresthesia of the foot should be carefully examined in FM patients.